On fast state-space algorithms for predictive control - Błachuta, Marian J. (Zielona Góra: Uniwersytet Zielonogórski)
A Riccati-equation-based solution to a class of receding-horizon predictive control problems for an explicit-delay state-space model of an ARMAX system is found and the corresponding vector Chandrasekhar-type equations are derived for both filter and controller gains to improve the computational efficiency.
Keywords: Riccati equation; Chandrasekhar equation; LQG control; predictive control